Methods of a New Chronic Pancreatitis and Spontaneous Pancreatic Cancer Mouse Model Using Retrograde Pancreatic Duct Injection of Dibutyltin Dichloride - Zhang, Deyu; Li, Wanshun; Wang, Meiqi; Yin, Hua; Xia, Chuanchao; Li, Keliang; Huang, Haojie (Frontiers in Oncology, 2022)
The current study aimed to develop a new chronic pancreatitis and spontaneous pancreatic cancer model on C57/BL6 mouse through retrograde pancreatic duct injection of dibutyltin dichloride (DBTC) and explore its basic pathological changes as compared to the previous published chronic pancreatitis model through tail vein injection of DBTC with alcohol drinking. C57/BL6 mice were randomly divided into 3 groups: CG (control group; n = 15), VG (tail vein injection of DBTC (8 mg/kg) with 10% alcohol drinking group; n = 20), and PG (retrograde pancreatic duct injection of DBTC group (1 mg/kg); n = 30). Five mice in each group were sacrificed at a specific time point after the first treatment. The pathological section was observed. The activities of amylase, bilirubin, and hyaluronic acid in serum were determined. The expression of fibronectin, COL1A1, α-SMA, MMP-1, and TIMP-1 in the pancreas was assayed. Severe fibrosis of the pancreas with inflammatory cell infiltration could be observed on day 21 in the PG. In the VG, slight fibrosis of the pancreas with inflammatory cell infiltration was observed on day 28. There were significant differences in serum amylase, bilirubin, and hyaluronic acid levels between the PG and VG. The protein level of COL1A1 and α-SMA significantly increased in the PG. The mRNA expression of TIMP-1 is upregulated and the MMP-1 mRNA level is downregulated in the PG. Finally, typical neoplastic pathological change is significantly obvious in the PG. In conclusion, we established and validated a new chronic pancreatitis (CP) and spontaneous pancreatic cancer mouse model through retrograde injection of DBTC into the pancreatic duct. Previously reported mouse model through tail vein injection of DBTC with alcohol drinking could not cause obvious CP and neoplastic pathological change in mice.